Resistance to paclitaxel induces glycophenotype changes and mesenchymal-to-epithelial transition activation in the human prostate cancer cell line PC-3 - Leonardo Marques da Fonseca; Danilo Macedo Calvalhan; Jose Osvaldo Previato; Lucia Mendonça Previato; Leonardo Freire-de-Lima (Tumor Biology)
The development of the multidrug resistance phenotype is one of the major challenges faced in the treatment of cancer. The multidrug resistance phenotype is characterized by cross-resistance to drugs with different chemical structures and mechanisms of action. In this work, we hypothesized that the acquisition of resistance in cancer is accompanied by activation of the epithelial-to-mesenchymal transition process, where the tumor cell acquires a more mobile and invasive phenotype; a fundamental step in tumor progression and in promoting the invasion of other organs and tissues. In addition, it is known that atypical glycosylations are characteristic of tumor cells, being used as biomarkers. We believe that the acquisition of the multidrug resistance phenotype and the activation of epithelial-to-mesenchymal transition provoke alterations in the cell glycophenotype, which can be used as glycomarkers for chemoresistance and epithelial-to-mesenchymal transition processes. Herein, we induced the multidrug resistance phenotype in the PC-3 human prostate adenocarcinoma line through the continuous treatment with the drug paclitaxel. Our results showed that the induced cell multidrug resistance phenotype (1) acquired a mixed profile between epithelial and mesenchymal phenotypes and (2) modified the glycophenotype, showing an increase in the level of sialylation and in the number of branched glycans. Both mechanisms are described as indicators of poor prognosis.